Optimization of Tourism Study Program Lecturers in Improving the Quality of Education at Triatma Mulya University Bali Indonesia - Sulastri, Ida Ayu Putu; Wiantara, I Gusti Nyoman (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study explores the optimization of tourism study program lecturers in enhancing education quality at Triatma Mulya University, Bali, Indonesia. It examines the impact of lecturer qualifications, teaching methodologies, and professional development on student learning outcomes. A quantitative study of 100 tourism students used stratified sampling to evaluate lecturer impact on educational quality. Data were analysed using SmartPLS 3 to evaluate the impact of lecturer qualifications on education quality The findings highlight that lecturer qualifications, innovative teaching methodologies, and continuous professional development significantly enhance the quality of education. Teaching methodologies, particularly experiential learning techniques, strongly influence student engagement and learning outcomes (β = 0,426). The study is limited to one institution, restricting generalizability to other educational contexts. Reliance on self-reported data introduces potential bias, and the cross-sectional design limits causal inferences. Future research should explore cross-cultural comparisons and the impact of emerging technologies on tourism education. Institutions should prioritize faculty development and industry collaboration, while policymakers should implement accreditation standards that mandate continuous professional development. The tourism industry can benefit by partnering with universities to shape curricula that align with workforce needs. This study provides a unique perspective on optimizing tourism education by integrating lecturer development strategies with industry-aligned curricula, offering valuable insights for educators, administrators, and policymakers in tourism education.